Outcomes and Complications of Ahmed Glaucoma Valve Implantation in Neovascular versus Other Secondary Glaucoma: A One-Year Follow-up Study: Doi: 10.36351/pjo.v41i1.1989 - Mirza, Aneeq Ullah Baig (Pakistan Journal of Ophthalmology, 2025)
Purpose: To compare the visual outcomes and intraocular pressure between patients with neovascular glaucoma (NVG) and other secondary glaucoma (OSG) one year after Ahmed glaucoma valve (AGV) implantation. Study design: Retrospective study. Place and Duration of Study: Islamic International Medical College/Railway Hospital Westridge Rawalpindi, from January 2015 to January 2022. Methods: Ahmed glaucoma valve (model FP7) was implanted in 54 patients with NVG and OSG. The preoperative and post-operative vision and IOP was compared between the two groups with one year follow up. Success was defined as IOP of 5-21 mmHg without topical therapy (complete success) or with topical therapy (qualified success), no loss of light perception and not requiring subsequent glaucoma surgery or tube removal. Results: After one year, the mean postoperative vision improved to 0.9385 from 1.25 LogMAR in NVG group and to 0.8143 from 0.8500 LogMAR in OSG group. The mean IOP reduced from 41.69 to 16.27mmHg in NVG group. While in OSG group it reduced from 33.39 to 12.857 mmHg one year postoperatively (p-value 0.0001). Hyphema was the commonest complication in NVG and hypertensive phase in the OSG. NVG group showed complete success in 2, qualified success in 18 and failure in 6 cases. In the second group, complete success was seen in 8, qualified success in 18 and failure in 2 cases. Conclusion: Ahmed glaucoma valve implantation is effective in saving useful vision andcontrolling IOP in majority of refractory glaucomas and the results are comparable between neovascular and other secondary glaucomas.